Civilian Uses of Hemoglobin-based Oxygen Carriers - Greenburg, A. Gerson; Kim, Hae Won (Artificial organs, 2004)
:  This article briefly discusses a few key issues related to transfusion, the concept of hemoglobin‐based red blood cell substitutes (HBOCs), and some parameters useful in evaluating the current properties of solutions. Potential uses of HBOCs in civilian applications are identified and listed. Use of HBOCs as a hemodiluent for intraoperative autologous blood donation (IAD) is a particular application that has relevance in many surgical settings and this is discussed in some detail. Data from a Phase III clinical trial is presented to show the potential for avoiding the use of allogeneic blood and blood products in a clinical model of large volume red cell use. Extrapolation to a general use model, primarily based in the potential for surgery, will be noted. Some general parametric values of HBOCs are presented. These  values  are  by  no  means  considered  optimal  for all HBOCs and are subject to exploration, fine tuning,   correction,   or even rejection.